A supramolecular probe for colorimetric detection of Pb2+ based on recognition of G-quadruplex. Issue 3 (4th December 2014) - Chen, Hongbo; Sun, Hongxia; Zhang, Xiufeng; Sun, Xiaoran; Shi, Yunhua; Tang, Yalin
Abstract : A colorimetric probe of Pb 2+ has been designed based on the mechanism that a supramolecular probe selectively recognized the Pb 2+ -induced conformational transition of G-quadruplexes. Abstract : A colorimetric probe of Pb 2+ has been designed based on the mechanism that a supramolecular probe selectively recognized the Pb 2+ -induced conformational transition of G-quadruplexes. The probe exhibited high sensitivity and selectivity towards Pb 2+, which enabled it to be practically used in detection of the Pb 2+ level in a freshwater system.